SISTEM IDENTIFKASI PENYAKIT TANAMAN CABAI MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) BERBASIS ANDROID - Hendire S B; Machudor Yusman (Universitas Lampung, 2021)
Chili is an important commodity in Indoneisa’s economy. The fluctuating price causes chili to contribute to inflation for national economy. Chili’s price could increase because of demand in high level and production of chili in low level. The emergence of disease causes production of chili decreas. To solve the problem in chili disease, the disease needs to be diagnose as soon as possible. To diagnose the disease as soon as possible there is a need of chili expert system using android. Chili’s disease will be indentificated by inputting the symptoms which are shown by the plan. Expert system of chili plant disease identification design is based Android. Android Mobile is used as a device to insert the symptoms which are shown by the plant. The system will manage the symptoms that have been selected and show the diagnoses of the disease and how to control the disease. This system was designed using the Simple Additive Weighting (SAW) method and tested using Blackbox method. Testing using Blackbox method to show the system is able to identify the diseases of chili plant